2017
DOI: 10.1007/s00484-017-1460-8
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic storm under laboratory conditions: randomized experiment

Abstract: The influence of the previously recorded geomagnetic storm (GS) on human cardiovascular system and microcirculation has been studied under laboratory conditions. Healthy volunteers in lying position were exposed under two artificially created conditions: quiet (Q) and storm (S). The Q regime playbacks a noise-free magnetic field (MF) which is closed to the natural geomagnetic conditions on Moscow's latitude. The S regime playbacks the initially recorded 6-h geomagnetic storm which is repeated four times sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The effect of MF variations on the human cardiovascular system in tested subjects has been demonstrated in observational [Alabdulgader et al, 2018] and laboratory studies with a simulation of previously recorded variations of the geomagnetic field [Gurfinkel et al, 2018; Pishchalnikov et al, 2019]. A lowering of the constant MF also affects humans [Sarimov et al, 2008; Binhi and Sarimov, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of MF variations on the human cardiovascular system in tested subjects has been demonstrated in observational [Alabdulgader et al, 2018] and laboratory studies with a simulation of previously recorded variations of the geomagnetic field [Gurfinkel et al, 2018; Pishchalnikov et al, 2019]. A lowering of the constant MF also affects humans [Sarimov et al, 2008; Binhi and Sarimov, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the smallness of the values of geomagnetic disturbances compared with urban MF, when comparing their integral powers over a wide range of 10 −5 –1 Hz, the correlations between magnetic storms and the state of the human organism are reliably established [Breus et al, 2016]. There is evidence of a direct effect of artificial magnetic storms on the human organism [Gurfinkel et al, 2018; Pishchalnikov et al, 2019], as well as on planktonic species [Krylov and Osipova, 2019].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the analysis of experimental data [Krylov et al, 2014; Martinez‐Breton and Mendoza, 2016; Gurfinkel et al, 2018] and the correlations between geomagnetic indices and biological processes [Chernouss et al, 2001; Gmitrov and Gmitrova, 2004; Azcaratea et al, 2016], it was previously suggested that geomagnetic storms could be perceived by organisms as a distortion of diurnal geomagnetic variation [Krylov, 2017; Krylov et al, 2019]. In other words, the inconsistency of circadian biochemical processes synchronized with light regime and diurnal geomagnetic variation may be responsible for the medical and biological effects of geomagnetic storms.…”
Section: Introductionmentioning
confidence: 99%